View Question
 Question
 Subject: Math Category: Miscellaneous Asked by: cleanncrazi-ga List Price: \$25.00 Posted: 20 Jul 2004 14:33 PDT Expires: 19 Aug 2004 14:33 PDT Question ID: 376836
 ```1) 2m^2+10m=-12 2)(a-2)(a-3)=6 3) 3/x+5/3x=1 4)3/t-3=5/t+4 5) m=r/1+rt for r 6) 3(square root) x+5=12 7)(square root) x^2+3x+6=4 solve by factoring 8) x^2-2x-24=0 9)2x^2+7x=4 solve by the quadratic formula 10) x^2-5x-6=0```
 ```Hi cleanncrazi, Here are the answers to your questions: 1. 2m^2+10m=-12 2m^2+10m+12=0 m^2+5m+6=0 (m+3)(m+2)=0 m=-3 and m=-2 2. (a-2)(a-3)=6 a^2-3a-2a+6=6 a^2-5a=0 a(a-5)=0 a-5=0 a=5 3. 3/x+5/3x=1 3/x+5/3x-1=0 3(3x)+5(x)-1(x)(3x)=0 9x+5x-3x^2=0 -3x^2+14x=0 x(-3x+14)=0 -3x=-14 x=14/3 4. 3/t-3=5/t+4 (3-3t)/t=(5+4t)/t 0= 5+4t-3+3t 0=2+7t -2=7t -2/7=t 5. m=r/1+rt for r (assuming this is meant to be m=r/(1+rt) m+rtm=r m=r-rtm m=r(1-tm) m/(1-tm)=r 6. 3sqrtx+5=12 9(x+5)=144 x+5=16 x=11 7. (square root) x^2+3x+6=4 x^2+3x+6=4^2 x^2+3x+6=16 x^2+3x-10=0 (x+5)(x-2)=0 x=-5, x=2 8. x^2-2x-24=0 (x+6)(x+4)=0 x=6, x=4 9. 2x^2+7x=4 2x^2+7x-4=0 (x+4)(2x-1)=0 x=-4, x=1/2 10. x^2-5x-6=0 x=-[(-5)+-sqrt[(-5)^2-4(1)(6)]]/2 x=[5+-sqrt(25+24)]/2 x=[5+-sqrt(49)]/2 x1=[5+sqrt(49)]/2 x1=(5+7)/2 x1=6 x2=[5-sqrt(49)]/2 x2=(5-7)/2 x2=-1 Questions 1, 8, and 9 were done using the simple factoring method as demonstrated at the following link: Purplemath - Factoring Quadratics Lesson - 1 http://www.purplemath.com/modules/factquad.htm I hope this helps! If you have any questions please feel free to ask for clarification. Regards, Deadlychiapet```
 cleanncrazi-ga rated this answer: `Very clear and concise work, thank you.`